Coupled Plasmonic Metallic Nanowires to Induce Localization of Surface Plasmon Polaritons (Bulletin of Pure and Applied Sciences – Physics, 2021)
We have studied the influence of the structural disorder on the spatial distribution of the  plasmonic field and its propagation in one and two dimensional arrays of coupled metallic  nanowires. By solving the three dimensional Maxwell equations we have studied the  Anderson localization of surface Plasmon polaritions for arrays of metallic nanowires with  varying degree of the structural disorder. We have found that a random distribution of radii of  the nanowires leaded to transverse spatial localization of collective surface plasmonic  polarition excitations. The characteristic spatial confinement of the plasmonic field found  smaller than the optical wavelength which demonstrated that plasmonic structures can be  employed to implement the subwave length Anderson localization of the electromagnetic  field. We have also found that influence of the metallic loss and the gain of the host medium  on the plasmonic Anderson localization modes, loss was compensated by the gain whose  strength was much smaller than the loss rate of the metallic component of the plasmonic  array. The obtained results were found in good agreement with previously obtained results.